Terminal Deoxynucleotidyl Transferase (TdT) Inhibiti on of Cord Blood Derived B and T Cells Expansion - Sanaz Gholami; Seyede Momeneh Mohammadi; Aliakbar Movasaghpour Akbari; Ali Abedelahi; Alireza Alihemmati; Shirin Fallahi; Hojjatollah Nozad Charoudeh (Tabriz University of Medical Sciences, 2017)
Purpose: Terminal deoxynucleotidyl transferase(TdT) is a DNA polymerase that is present in immature pre-B and pre-T cells. TdT inserts N-nucleotides to the V (D) J gene segment during rearrangements of genes, therefore, it plays a vital role in the development and variation of the immune system in vertebrates. Here we evaluated the relationship between cytokines like interleukin-2 (IL-2), interleukin-7 (IL-7), and interleukin-15 (IL-15) and TdT expression in cord blood mononuclear cells and also effect of inhibition in the expansion of B and T cells derived from cord blood. Methodes: The cord blood mononuclear cells were cultured with different combination of cytokines for 21days, which they were harvested in definite days (7, 14 and 21) and evaluated by flow cytometry. Results: Our data indicated that TdT expression increased in cord blood mononuclear cells using immune cell key cytokines without being dependent on the type of cytokines. TdT inhibition reduced both the expansion of B and T cells derived from cord blood and also declined the apoptosis and proliferation. Considered together, TdT played an important role in the control of the expansion of B and T cells derived from cord blood. Conclusion: considered together, it was observed that TdT expression was increased by cytokines and TdT inhibition not only reduced B and Tcells derived from cord blood, but it also affected the rate of apoptosis and proliferation.